Studi Living Qur’an tentang Implementasi Program Baca Tulis Qur’an melalui Tradisi Literasi Al-Qur’an di MAN 1 Gunungkidul - Jauharotun Nafiisah; Ahmad Hanany Naseh; Muh Aufal Minan; Ridhoul Wahidi (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2021)
Al-Qur'an is the word of Allah, which is eternal and has no equal. The content of the Qur'an contains all scopes of knowledge. The Qur'an as the basis for teaching also provides inspiration, motivation, and contribution in building and developing various knowledges through verses that command to read, write, explore, memorize, interpret, and understand the Qur'an in the same sense broadly. This meaning is commonly referred to as Al-Qur'an literacy. This study uses descriptive research with a qualitative approach through a case study at MAN 1 Gunungkidul. The data collection is done by interview with informants and library research from various literature sources in accordance with the research theme. Based on the results of the study, the concept of Al-Qur'an literacy includes the implementation process of determining the schedule, time and place of implementation, and the parties involved; the practice of developing the Qur'anic literacy tradition; and its contribution to the potential development and success of students. Thus, learning the Qur'an, including moral education, is expected to create a generation who loves the Qur'an accompanied by practical practices in everyday life.